The dynamic effects of maternal high-calorie diet on glycolipid metabolism and gut microbiota from weaning to adulthood in offspring mice - Zheng, Jia; Zhang, Ling; Gao, Ying; Wu, Honghua; Zhang, Junqing (Frontiers in Nutrition, 2022)
Dysbiosis of gut microbiota can contribute to the progression of diabetes and obesity. Previous studies have showed that maternal high fat (HF) diet during the perinatal period can alter the microbiota and induce metabolic disorders at weaning. However, whether the dysbiosis of gut microbiota and metabolism could be recovered by a normal diet after weaning and the dynamic changes of gut microbiota have not been fully studied. In this study, C57BL/6J female mice were fed with a normal chow (NC) or HF diet for 4 weeks preconception, during gestation, and until pup weaning. After weaning, male offspring were fed with a NC diet until 9 weeks of age. The microbiota of offspring at weaning and 9 weeks of age was collected for 16S rRNA gene amplicon sequencing. We found that dams fed with an HF diet showed glucose intolerance after lactation. Compared with the offspring from NC dams, the offspring from HF dams exhibited a higher body weight, hyperglycemia, glucose intolerance, hyperinsulinemia, hypercholesterolemia, leptin resistance and lower adiponectin at weaning. Fecal analysis indicated altered microbiota composition between the offspring of the two groups. The decrease in favorable bacteria (such as norank f Bacteroidales S24-7 group) and increase in unfavorable bacteria (such as Lachnoclostridium and Desulfovibrio) were strongly associated with a disturbance of glucose and lipid metabolism. After 6 weeks of normal diet, there was no difference in body weight, glucose and lipid profiles between the offspring of the two groups. However, microbiota composition of offspring in the HF group was still different from that in the NC group and microbiota diversity was lower in offspring of the HF group. The abundance of Lactobacillus was lower in the offspring of the HF group. In conclusion, a maternal HF diet can induce metabolic homeostasis and gut microbiota disturbance in offspring at weaning. Gut microbiota dysbiosis can persist into adulthood in the offspring, which might have a role in the promotion of susceptibility to obesity and diabetes in the later life of the offspring.